BOOKSTORE MANAGEMENT SYSTEM FOR R.B AHMAD BOOKSHOP - Suriantih, Suddin (Universiti Malaysia Sarawak, (UNIMAS), 2020)
This work aims to describe the proposed system of Bookstore Management System for R.B Ahmad Bookshop. The development of the proposed system is to change the manual method to computerized system. The problem arise where customer complaint as they unable to order book through online. And for every ordering/purchasing book is recorded manually where might cause the document missing or misplace that difficult to the staff to make references. This proposed system aims to solve the matters and ease the staff as well as the customer and it also can save more time. Apart from this, the methodology used in this system is Rapid Application Development (RAD). The significance of this project is to facilitate staff to manage the record of ordering/purchasing book and customer for them to order/purchase book through online.